Fish kept in the open on a sheet under direct sunlight - Mumbai Archive Project Team (Jio Institute, 2024)
Dried fish retains much of its nutritional value, including protein and omega-3 fatty acids, which makes it a valuable low-cost nutrition source, particularly in regions where fresh fish may be unavailable or expensive.